PENGARUH ONLINE GROCERY DELIVERY SERVICE, PRODUCT QUALITY, DAN PRODUCT KNOWLEDGE TERHADAP CUSTOMER SATISFACTION PADA APLIKASI ALFAGIFT - Azra Putri Anaztasya; Hania Aminah; Diena Noviarini (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2025)
This study aims to evaluate the extent to which online grocery delivery service, product quality, and product knowledge influence customer satisfaction among users of the Alfagift application. The research adopts a quantitative approach, targeting a population consisting of Generation Y and Z individuals residing in the Greater Jakarta area (Jabodetabek) who have made at least one purchase using the Alfagift app. The sampling technique employed is purposive sampling, involving a total of 200 respondents. Data collection was carried out online via Google Forms, using a questionnaire comprising 40 indicators. A Likert scale was utilized to measure the respondents’ level of agreement with each statement. For data analysis, the study applies the Structural Equation Modeling method using the Partial Least Squares approach (SEM-PLS), which aims to assess the relationships between variables within the proposed model. The study formulated three main hypotheses, all of which were accepted based on statistical analysis results indicating significant relationships. The findings of this research demonstrate that the three independent variables—online grocery delivery service, product quality, and product knowledge—positively and significantly impact customer satisfaction among Alfagift users. Therefore, this study highlights the importance of service optimization, product quality enhancement, and consumer education in increasing customer loyalty and satisfaction in digital shopping platforms such as Alfagift.